The database TABVERK - Demographic database, Umeå university (Umeå University, 2014)
The database TABVERK contains population statistics in the Swedish parishes during the period 1749-1859. It constitutes the earliest population statistics throughout the world making it a unique source. Merely in Finland, a similar time serial of data exists. The database gathers all the information about the parishes’ populations that Swedish clergymens filled out in large forms of tables which were reported to the Tabellkommissionen in Stockholm. Now this information is accessible through the agency of the Demographic Data Base.

The database contain information on births, deaths, marriage, and occupation. The population is describe by sex, age, civil status, and by occupation and social status every fifth year. Yearly statistics is given about the demographical events, fertility, mortality and nuptiality, as well as migrations in the 19th century. The statistics in Tabellverket (TABVERK) enable demographical studies from several angles on both local and regional level in Sweden during the pre-industrial society.

TABVERK holds an online search tool called SHiPS (Swedish Historical Population Statistics), which can be reached and utilized from the home page of the Demographic Data Base.

Purpose:

The Demographic Database (DDB) is a special unit at Umeå University with activities focused on two main areas: data production and research. DDB creates and makes available population databases, mainly based on historical information in parish registers during the 18th, 19th, and 20th centuries.

Tabellverksdatabasen innehåller statistik om befolkningen i Sveriges samtliga församlingar under åren 1749 till 1859. Det är den tidigast förda befolkningsstatistiken i hela världen, nära nog unik i sitt slag. Endast i Finland finns motsvarande statistiska data. Databasen samlar alla de uppgifter om församlingarnas befolkning som svenska präster fyllde i på stora formulär och sände in till Tabellkommissionen i Stockholm. Denna befolkningsstatistik är tillgänglig för allmänheten via Demografiska databasen.

Tabellverksdatabasen innehåller exempelvis uppgifter om födda, döda, vigda och yrken. Vart femte år redovisas folkmängden efter kön, ålder, civilstånd, yrken och ståndstillhörighet. Årliga uppgifter finns däremot om fertilitet, mortalitet och giftermål, samt under 1800-talet även om flyttningar. Denna statistik gör det möjligt att studera olika demografiska förhållanden i det förindustriella Sverige.

Du kan själv söka data ur Tabellverksdatabasen med hjälp av verktyget SHiPS, som finns på Demografiska databasens webbsida.

Syfte:

Demografiska databasen (DDB) är en särskild enhet vid Umeå universitet med inriktning på dataproduktion och forskning. DDB skapar och tillgängliggör befolkningsdatabaser, främst baserade på historisk information från kyrkböcker från 1700-, 1800- och 1900-talen.
Tabellverksdatabasen - Demografiska databasen
Keywords: childbirth; barnafödsel; census data; folkräkningsdata; demography; demografi; demographic statistics; demografisk statistik; birth rate; födelsetal; migrants; migranter; mortality rate; dödstal; vital statistics; befolkningsstatistik; marriage rate; äktenskapsfrekvens; SwedPop; SwedPop; DEMOGRAPHY (POPULATION, VITAL STATISTICS, AND CENSUSES); DEMOGRAFI (POPULATION, VITALSTATISTIK OCH FOLKRÄKNINGAR); Censuses; Folkräkningar; History; Historia